KORELASI SIKAP DAN NORMA SUBJEKTIF TERGADAP PERILAKU SEKSUAL BERISIKO PADA REMAJA - Aisyah, Aisyah; Jessica Rotinsulu, Ria Angelina; Erni, Erni; L.Tobing, Hendri Parluhutan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Adolescents are an age group that is considered to be at high risk for various risky behaviors in the context of modern social interaction. Risky sexual behavior in adolescents is a phenomenon that is influenced by various interacting factors. The purpose of this study was to determine the correlation between attitudes and subjective norms towards risky sexual behavior in adolescents. A cross-sectional design was used in this study. The research was conducted in several high schools in Manado City. The research was conducted in March 2025. The population consisted of all students in several high schools in Manado. The sample consisted of 76 people. The sampling technique used probability sampling. The research instrument used a research questionnaire. Data analysis was performed using univariate and bivariate analysis. The results showed a relationship between attitudes (p value: 0.042) and subjective norms (p value: 0.016) with sexual behavior in adolescents. It is recommended that adolescents increase their knowledge. Health workers, teachers, and parents are expected to increase efforts in sexuality and reproductive health education so that adolescents can maintain their social interactions in the community by knowing which behaviors are good and which are not. Keywords: Adolescents, Attitudes, Subjective Norms